Unravelling the gut microflora landscape of broilers by high-throughput next generation sequencing - Mohd Asrore, Mohd Shaufi; Sieo, Chin Chin; Chong, Chun Wie; Gan, Han Ming; Ho, Yin Wan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Normal gut microflora plays an important function in nutrient absorption, feed digestion and modulation of immune response in the birds. Earlier, gut microflora were studied based on traditional cultivation and molecular fingerprinting methods. However, low sensitivity, coverage, accuracy and reproducibility have shift researcher to high-throughput next-generation sequencing (HT-NGS) technology, which enable a better gut microflora study approach due to high coverages and depths of sequencing. Briefly, chicken gut microflora of the ilea and caeca were studied at various time points, day 7, 14, 21 and 42-day-old. DNA extraction was performed, amplified based on V3 hypervariable region of 16S rRNA, sequenced and analysed. The communities of broiler gut microflora in caeca were significantly different in comparison to ilea (P < 0.001). In addition, their communities subsequently became more diverse as chicken aged from day 7, 14, 21 until 42-day-old. The caeca had more diverse gut microflora compared to ilea, with low communities of Lactobacillus and high communities of Clostridium. Based on gene predictions study, gene pathways related to nutrient absorption (e.g. amino sugar nucleotide sugar metabolism), and bacterial proliferation and colonisation (e.g. two-component system, bacterial motility proteins and secretion system) were observed to be dominant in ilea and caeca, respectively (P < 0.05). In conclusion, gut microflora of ilea and caeca were unique in which they performed different roles and functions. The low presence of beneficial microbes (e.g. Lactobacillus) and high presence of potential pathogens (e.g. Clostridium) in the broiler intestines highlighted the needs of gut modulation to further improve the gut health.